2021
DOI: 10.1016/j.heliyon.2021.e07833
|View full text |Cite
|
Sign up to set email alerts
|

A participatory epidemiological investigation of causes of cattle abortion in Jimma zone, Ethiopia

Abstract: A participatory epidemiological study was conducted with cattle keepers in Jimma zone, Ethiopia, between October 2018 and October 2019 to identify the causes of abortion in cattle. Data collection involved 20 group discussions (each comprising 8–12 people) in 10 peasant associations. Methods used in group discussions included semi-structured interviews, pairwise ranking, matrix scoring, proportional piling, and seasonal calendar. The result of pairwise ranking identified brucellosis, leptospirosis, listeriosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 30 publications
13
10
0
Order By: Relevance
“…The overall impression of the diagnostic laboratory data supplied was that it lacked detail and did not appear comprehensive, rather providing a reflection of the general causes of mortality and reproduction losses. A recent study reported that a lack of diagnostic laboratory resources, combined with the presence of most potential infectious and non-infectious causes of abortion made diagnosis particularly challenging in Ethiopia ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall impression of the diagnostic laboratory data supplied was that it lacked detail and did not appear comprehensive, rather providing a reflection of the general causes of mortality and reproduction losses. A recent study reported that a lack of diagnostic laboratory resources, combined with the presence of most potential infectious and non-infectious causes of abortion made diagnosis particularly challenging in Ethiopia ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other likely sources of natural variation in the datasets include different conditions for different years, such as droughts and epidemics ( 32 , 33 ). That there was evidence of spatiotemporal variation of risk factors and causes of mortality is not surprising, as seasonal and environmental variation affects grazing availability and ensuing movement and mixing of animals ( 31 , 34 , 35 ) which can then affect disease transmission. A recent systematic review observed a scarcity of disease-associated mortality data for Ethiopia, with only 14 studies identified [( 36 ), under review].…”
Section: Discussionmentioning
confidence: 99%
“…Other likely sources of natural variation include different conditions for different years, such as droughts and epidemics (Alemayehu and Fantahun, 2012; Megersa et al, 2014). That there was evidence of spatiotemporal variation of risk factors and causes of mortality is not surprising, as seasonal and environmental variation affects grazing availability and ensuing movement and mixing of animals (Devereux, 2006; Getachew et al, 2010; Gelalcha et al, 2021) which can then affect disease transmission. A recent systematic review observed a scarcity of disease-associated mortality data for Ethiopia, with only 14 studies identified (Tsouloufi et al, 2022, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…Several key informants recommended the strengthening of regional laboratories by fulfilling equipment needs and necessary funding, and suggesting that laboratories needed to strengthen their diagnostic capacity. A recent study reported that a lack of diagnostic laboratory resources, combined with the presence of most potential infectious and non-infectious causes of abortion made diagnosis particularly challenging in Ethiopia (Gelalcha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine leptospirosis is characterized mostly by reproductive losses such as abortions and stillbirths, as well as poor weight growth, mastitis, and reduction in milk yield. Nevertheless, laboratory testing, primarily serological techniques, are used to support the diagnosis 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%